Gender matters in global politics : a feminist introduction to international relations - Shepherd, Laura J. (London : Routledge, 2015)
'Gender Matters in Global Politics is a comprehensive textbook for advanced undergraduates studying feminism & international relations, gender and global politics and similar courses. It provides students with an accessible but in-depth account of the most significant theories, methodologies, debates and issues. This textbook is written by an international line-up of established and emerging scholars from a range of theoretical perspectives, providing students with provocative and cutting-edge insights into the study and practices of (how) gender matters in global politics. Key features and benefits of the book: Introduces students to the wide variety of feminist and gender theory and explains the relevance to contemporary global politics Explains the insights of feminist theory for a range of other disciplines including international relations, international political economy and security studies Addresses a large number of key contemporary issues such as human rights, trafficking, rape as a tool of war, peacekeeping and state-building, terrorism and environmental politics Features extensive pedagogy to facilitate learning seminar exercises, text boxes, photographs, suggestions for further reading, web resources and a glossary of key terms, new chapters on Environmental politics and ecology; War; Terrorism and political violence; Land, food and water; International legal institutions; Peacebuilding institutions and postconflict reconstruction; Citizenship; Art, aesthetics and emotionality; and New social media and global resistance In this innovative and groundbreaking textbook gender is represented as a noun, a verb and a logic, allowing both students and lecturers to develop a sophisticated understanding of the crucial role that gender plays in the theories, policies and practices of global politics.'--
'Gender Matters in Global Politics 2nd edition is a comprehensive textbook for advanced undergraduates studying feminism & international relations, gender and global politics and similar courses. It provides students with an accessible but in-depth account of the most significant theories, methodologies, debates and issues'--
Includes bibliographical references : p. 407-476 and index.
Keywords: International relations; Feminism; Feminist theory